Respuesta :
y=mc2 because 12 has to equal 6 then of cause he is going to minus it up
5y+12=6-y
We see that we have an unknown number (which is y) that we are multiplying by 5
5y
Then we see that it is increased by 12 (add 12)
5y+12
Our first part is equal to 6 decreased by the number y (subtract y from 6)
5y+12=6-y
:)
We see that we have an unknown number (which is y) that we are multiplying by 5
5y
Then we see that it is increased by 12 (add 12)
5y+12
Our first part is equal to 6 decreased by the number y (subtract y from 6)
5y+12=6-y
:)